Active tactile exploration for adaptive locomotion in the stick insect - Schütz, Christoph (The Royal Society, 2011)
Insects carry a pair of actively movable feelers that supply the animal with a range of multimodal information. The antennae of the stick insect Carausius morosus are straight and of nearly the same length as the legs, making them ideal probes for near-range exploration. Indeed, stick insects, like many other insects, use antennal contact information for the adaptive control of locomotion, for example, in climbing. Moreover, the active exploratory movement pattern of the antennae is context-dependent. The first objective of the present study is to reveal the significance of antennal contact information for the efficient initiation of climbing. This is done by means of kinematic analysis of freely walking animals as they undergo a tactually elicited transition from walking to climbing. The main findings are that fast, tactually elicited re-targeting movements may occur during an ongoing swing movement, and that the height of the last antennal contact prior to leg contact largely predicts the height of the first leg contact. The second objective is to understand the context-dependent adaptation of the antennal movement pattern in response to tactile contact. We show that the cycle frequency of both antennal joints increases after obstacle contact. Furthermore, inter-joint coupling switches distinctly upon tactile contact, revealing a simple mechanism for context-dependent adaptation.